2010
DOI: 10.1007/s11192-010-0305-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting inter-regional academic scientific collaboration within Europe: the role of economic distance

Abstract: This paper offers some insights into scientific collaboration (SC) at the regional level by drawing upon two lines of inquiry. The first involves examining the spatial patterns of university SC across the EU-15 (all countries belonging to the European Union between 1995 and 2004). The second consists of extending the current empirical analysis on regional SC collaboration by including the economic distance between regions in the model along with other variables suggested by the extant literature. The methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
2
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 18 publications
0
49
2
9
Order By: Relevance
“…Drawing upon this line of research, Boschma (2005), from a theoretical point of view, identified five kinds of proximities: geographical, cognitive, institutional, organizational, and social. Recent research has also highlighted the relevance of economic differences as an explanatory factor of SC (Acosta et al, 2011a;Hwang, 2008;Sonnenwald, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Drawing upon this line of research, Boschma (2005), from a theoretical point of view, identified five kinds of proximities: geographical, cognitive, institutional, organizational, and social. Recent research has also highlighted the relevance of economic differences as an explanatory factor of SC (Acosta et al, 2011a;Hwang, 2008;Sonnenwald, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Differences in economic resources among geographic areas (economic distance) may determine the spatial patterns in SC, as derived from the centre-periphery hypothesis (Schott, 1998;Schubert and Sooryamoorthy, 2010) applied to research collaboration (Acosta et al, 2011a). According to this literature, scientists in peripheral countries are willing to collaborate with core countries to gain access to resources, while core areas seeking complementarities (Hwang, 2008;Sonnenwald, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The main channel for spillovers in research is through collaboration, where several factors such as specialization, sharing the same language or culture, or the economic distance can promote or hinder collaboration (Acosta et al, 2011b), but not the fact that they share a border. Below we discuss the empirical results in detail and perform additional econometric robustness checks.…”
Section: Model and Variablesmentioning
confidence: 99%